Deciphering culturally-coded institutional responses to COVID-19 adversity and anti-Asian hate in higher education - Wang, Shu-wen; Chang, Janet; Benjamin, Laurel R.; Ni, Xueting; Walsh, Erin (Frontiers in Psychology, 2025)
IntroductionCultural values and belief systems are reflected in gateway contexts in societies, including educational settings. Yet, little is known about how values and norms are instantiated in higher education messages and how they may vary across cultural contexts during a global public health crisis. In this cross-cultural qualitative study, we examined cultural values and norms embedded in institutional messages at the early outset of the COVID-19 pandemic, exploring between-culture variations using an independence-interdependence framework. We also explored whether US higher education institutions addressed anti-Asian hate.MethodsWe coded and analyzed early institutional announcements addressing the COVID-19 pandemic from the top 100 US universities and liberal arts colleges as well as 20 universities in China.ResultsThematic analysis revealed cultural similarities in Chinese and US institutional emphases on following political and medical authorities and collaboration. US institutions stressed support for students, “future as uncertain” appraisals, assurance of academic success, and validation of students’ emotions in line with soft independence. In contrast, Chinese universities promoted compliance, moral duty, and individual responsibility for a collective problem in line with interdependence. Few US institutions acknowledged Asians/Asian Americans as being targets of racial bias or discrimination, yet some announcements also implicitly linked COVID-19 with China or Asia (e.g., travel warnings and origin statements).DiscussionFindings illuminate the cultural patterning of norms, values, and priorities in different contexts in response to the same global event and demonstrate both the invisibility and hypervisibility of Asians/Asian Americans during a racialized global pandemic.Public significance statementSelect higher education institutions in the US and China emphasized political/medical authority and collaboration in announcements addressing the COVID-19 pandemic. US institutions tended to focus on independent needs and norms (student support, emotional validation, assurance of academic success) and framed the future as being uncertain, while Chinese universities stressed interdependent messages about compliance as well as moral duty and individual responsibility for a collective problem. Most US institutions overlooked Asians/Asian Americans as being potential targets of racial bias or discrimination in the context of the pandemic, yet some institutions implicitly linked COVID-19 to China or Asia.